Implementation of Twitter in Spanish political environments: Transformation of the processes of democratic participation and of the communicative paradigm - Zazo Correa, Laura (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The irruption of Twitter in the Spanish political sphere and the arrival of political parties on the Internet has transformed the democratic process. Now, the citizen can also issue information and participate in social dialogue. Thus, Twitter becomes a communication channel that allows a direct conversation between politicians and citizens to be established. This article seeks to analyze the implementation of Spanish political parties on Twitter and study how their relationship with citizens has been transformed in order to assess the real degree of conversation that takes place on Twitter between politicians and citizens.